Kilka uwag o wpływie hezychazmu na przedstawienie chrztu Chrystusa na przykładzie sztuki z terenów Królestwa Serbii - Piórecka, Agnieszka (Vox Patrum, 2018)
The influence of hesychasm on representation on Christ’s baptism isn’t so obvious as in the case of transfiguration, anastasis or koimesis. On the contrary to the mentioned above, it hasn’t had its own study. We can assume, that the rise of interest in hesychasm during the kingship of Milutin is connected to Milutin’s programme of translation important theological and philosophical texts into Serbian language. In all referred images, we can see a manifestation of the mystical light of God. In the case of transfigurations, koimesis and anastasis, this light is illustrated by mandorla (almond-shaped aureole) around Christ. In depictions of baptism, mandorla surround the dove of the Holy Spirit. In the Serbian art mandorla takes, repeatedly, very complicated shapes. Additionally, in the baptism and koimesis scenes, above Christ’s head, appear open doors of Heaven. This can emphasise presence of God.